The Temporomandibular Joint of the Domestic Dog (Canis lupus familiaris) in Health and Disease. (May 2018) - Lin, A.W.; Vapniarsky, N.; Cissell, D.D.; Verstraete, F.J.M.; Lin, C.H.; Hatcher, D.C.; Arzi, B.
Summary: This study aimed to characterize the histological, biomechanical and biochemical properties of the temporomandibular joint (TMJ) of the domestic dog in health and disease. In addition, we sought to identify structure–function relationships and to characterize TMJ degenerative lesions that may be found naturally in this species. TMJs ( n  = 20) from fresh cadaver heads ( n  = 10) of domestic dogs were examined macroscopically and microscopically and by cone-beam computed tomography. The TMJ discs were evaluated for their mechanical and biochemical properties. If TMJ arthritic changes were found, pathological characteristics were described and compared with healthy joints. Five (50%) dogs demonstrated macroscopically normal fibrocartilaginous articular surfaces and fibrous discs and five (50%) dogs exhibited degenerative changes that were observed either in the articular surfaces or the discs. In the articulating surfaces, these changes included erosions, conformational changes and osteophytes. In the discs, degenerative changes were represented by full-thickness perforations. Histologically, pathological specimens demonstrated fibrillations with or without erosions, subchondral bone defects and subchondral bone sclerosis. Significant anisotropy in the TMJ discs was evident on histology and tensile mechanical testing. Specifically, the discs were significantly stiffer and stronger in the rostrocaudal direction compared with the mediolateral direction. No significant differences were detected in compressive properties of different disc regions. Biochemical analyses showed high collagen content and low glycosaminoglycan (GAG) content. No significant differences in biochemical composition, apart from GAG, were detected among the disc regions. GAG concentration was significantly higher in the central region as compared with the caudal (posterior) region. The TMJ of the domestic dog exhibits similarities, but also differences, compared with other mammals with regards to structure–function relationships. The TMJ articular surfaces and the disc exhibit degenerative changes as seen in other species, including perforation of the disc as seen in man. The degenerative changes had greater effects on the mechanical properties compared with the biochemical properties of the TMJ components. Translational motion of the TMJ does occur in dogs, but is limited.